Balanced Security and Privacy Protection in Digital Content Distribution Systems - Prihandoko, Antonius Cahya; Pinasthika, Stanislaus Jiwandana; Ghodosi, Hossein (Jurnal Teknologi dan Manajemen, 2025)
Security protection for content providers is essential in a digital content distribution system so that only authorized users can access the content. However, focusing on the security aspect often makes the system ignore the privacy of content users. This article presents a model of protocol that can provide balanced protection of content provider security and user privacy in a digital content distribution system. This protocol is based on oblivious transfer (OT), a standard protocol in cryptography that allows the sender of a message to send a certain amount of information securely to the recipient of the message, such that at the end of the protocol the recipient of the message cannot access more information than specified, while the sender of the message cannot know which information was successfully accessed by the recipient. Assuming the existence of tamper-proof devices, the protocol presented in this article can provide excellent protection for both the security of content providers and the privacy of content users.